2021
DOI: 10.3390/infrastructures6120176
|View full text |Cite
|
Sign up to set email alerts
|

Application of Digital Image Correlation in Structural Health Monitoring of Bridge Infrastructures: A Review

Abstract: A vision-based approach has been employed in Structural Health Monitoring (SHM) of bridge infrastructure. The approach has many advantages: non-contact, non-destructive, long-distance, high precision, immunity from electromagnetic interference, and multiple-target monitoring. This review aims to summarise the vision- and Digital Image Correlation (DIC)-based SHM methods for bridge infrastructure because of their strategic significance and security concerns. Four different bridge types were studied: concrete, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…This study proposed an accurate method for full-field vibration measurement. The method is based on projected 3D-DIC and is capable of non-invasively identifying the full-field mode shapes and natural frequencies of a UAV wing made of composite material, which could potentially benefit structural dynamics and health monitoring applications [54]. Previous studies described fringe patterns [55,56], laser speckle [41,57] or a combination of both [40] to create a non-invasive pattern for full-field vibration measurement in DIC applications.…”
Section: Discussionmentioning
confidence: 99%
“…This study proposed an accurate method for full-field vibration measurement. The method is based on projected 3D-DIC and is capable of non-invasively identifying the full-field mode shapes and natural frequencies of a UAV wing made of composite material, which could potentially benefit structural dynamics and health monitoring applications [54]. Previous studies described fringe patterns [55,56], laser speckle [41,57] or a combination of both [40] to create a non-invasive pattern for full-field vibration measurement in DIC applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SHM has been accomplished by the analysis of images and videos taken by modern sensors such as cameras, robotic sensors, telephones, and drones [20]. Regardless of the type of sensor, the accuracy of the existing damage diagnosis and localization algorithms heavily depends on the accessibility of several high-quality sensors and datasets.…”
Section: Related Workmentioning
confidence: 99%
“…They used the El Carrizo Bridge as a case study, and their results showed the precision of PPP-GNSS measurement technology as well as the potential advantages of the alternative probabilistic SHM technique. Mousa et al [36] provided an overview of the vision and digital image correlation (DIC)-based SHM techniques for bridges. In their study, they considered different kinds of bridges, such as concrete, suspension, masonry, and steel bridges.…”
Section: The Importance Of Using the Shm Systemmentioning
confidence: 99%